Healthy lifestyle interventions in general practice Part 8: Lifestyle and dyslipidaemia - Martin Schwellnus; D.N. Patel; C. Nossel; M. Dreyer; S. Whitesman; E.W. Derman (South African Family Practice)
Dyslipidaemia, in particular raised plasma concentrations of total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), triglycerides as well as reduced plasma concentrations of high density lipoprotein (HDL-C) concentration is one of the major risk factors for coronary artery disease (CAD), cerebrovascular disease and peripheral vascular disease. The clinical assessment of a patient with suspected dyslipidaemia should include a medical history, clinical examination and special investigations to determine the presence and cause of dyslipidaemia, and to perform a risk assessment for cardiovascular disease using specific guidelines. Based on the risk scoring and the plasma lipid concentrations, an individualised management plan can be established for each patient. The focus of this article is on the cornerstone of management of dyslipidaemia which is lifestyle intervention. Lifestyle intervention for dyslipidaemia includes dietary intervention, increased physical activity, stress management and smoking cessation.